Sistem Pendeteksi Sampah Secara Realtime Menggunakan Metode YOLO - Priana, Kadek Adi; Eka Karyawati, Anak Agung Istri Ngurah (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 1 (2023): JNATIA Vol. 2, No. 1, November 2023DO - 10.24843/JNATIA.2023.v02.i01.p04, 2023)
At present, people’s daily garbage is increasing day by day. How to intelligently classify garbage can save manpower and improve work efficiency. In this paper, a garbage classification model is based on. First, according to the common daily garbage category, twelve typical kinds of garbage were selected, data cleaned, labeled, and constructed a garbage dataset. Second, YOLO was built and trained on our datasets. The experimental results show that YOLO can accurately identify the garbage’s types and find out the location of garbage.